SIMULATION OF DISPOSAL SLOPE DESIGN USING THE SPENCER METHOD IN THE SOFT MATERIAL AREA OF PT XYZ, BERAU, EAST KALIMANTAN - Afiah, Mahda; Muslim, Dicky; Fachrudin, Kurnia Arfiansyah; Anhar, Jevye Fazrin Kusumah (Faculty of Geological Engineering, Universitas Padjadjaran, 2024)
PT XYZ is a coal mining company utilizing an open-pit mining system, currently serving as the subject of this research. Every mining activity requires a disposal area to place the residual materials covering the mineral deposits. This study aims to analyze the disposal slope's stability in accordance with KEPMEN ESDM No.1827 Tahun 2018. The slope design simulations were conducted using limiting variables, like the bench angle of 35°, bench heights of 5 meters and 10 meters, and bench widths of 10 meters, 20 meters, and 30 meters. Input data comprised material properties such as unit weight, cohesion, and internal friction angle for materials including soft clay, dense clay, bund wall, and waste. The data was obtained by tests on basic physical properties and triaxial compression tests. The conditions assumed the slope was saturated groundwater level while considering the earthquake coefficient. This research employed the Spencer method for slope stability analysis, resulting in a safe and volumetrically efficient slope design with bench angle angle of 35°, bench heights of 5 meters, and bench widths of 30 meters with the safety factor 1,11.